MENGHIDUPKAN KEMBALI PERMAINAN TRADISIONAL: MENINGKATKAN MOTIVASI BELAJAR DALAM PENDIDIKAN JASMANI SEKOLAH DASAR MELALUI PERMAINAN BERBASIS BUDAYA - Ainur Rofi; Anung Priambodo; Pudjijuniarto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Low student motivation in Physical Education, Sports, and Health remains a significant challenge at the elementary school level. The learning process often becomes monotonous, and the limited exploration of local cultural values results in a lack of enthusiasm among students for participating in learning activities. This study aims to analyze the impact of traditional culture-based games on student learning motivation within PJOK education. The methodology employed is quantitative, utilizing a quasi-experimental design featuring a one-group pretest-posttest approach. The research subjects included 19 fifth-grade students from SDN Bleberan in Mojokerto. A learning motivation questionnaire served as the instrument, administered both prior to and following the treatment. The results of the hypothesis testing, conducted using the Wilcoxon Signed Rank Test, revealed a significance value of 0.000 (<0.05), indicating a significant effect on enhancing learning motivation after the introduction of traditional games. Traditional games have demonstrated pedagogical potential as an engaging, contextual, and effective medium for increasing student motivation in Physical Education, Sports, and Health at the elementary school level.